(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this article are presented and explained three maps on the celtiberian tesserae of hospitality: 1.- Map of the distribution of findings; 2.- Map of the distribution of civic communities mentioned in the inscriptions; 3.- Map of the relationship between the communities documented in the tesserae.